Reforming Vietnamese Higher Education Global Forces and Local Demands - Nguyen, Nhai Thi; Tran, Ly Thi (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2019)
XXV, 267 p. 6 illus.